Gambaran Kisah Inspiratif Dengan Menggunakan Majas Dan Citraan Dalam Puisi “If” Karya Rudyard Kipling - Novira Kania Hermiliany (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2023)
From the various studies that have been carried out, it can be observed that study on figurative language with stylistic studies has been studied extensively. Although there are many studies on figure of speech and imagery with stylistic studies, the writer believes that the same study still needs to be done. The writer does this to complement and add to previous stylistic studies. Relevant theories are used in this study to assist the results of the analysis to be obtained. The purpose of this study is to describe an inspiring story using various figures of speech and imagery contained in the poem